The Development of A Tri-Nga Integrated Problem Based Learning Science Module to Increase Student Independence - Sistiati, Heni (Universitas Sarjanawiyata Tamansiswa, 2025)
This study was motivated by the low student independence, the lack of variety of learning models used by teachers and the unavailability of learning modules that support IPAS learning. This research aims to: (1) produce an IPAS module based on problem-based learning integrated with Tri-Nga; (2) test the feasibility of the IPAS module based on problem-based learning integrated with Tri-Nga; and (3) test the effectiveness of the IPAS module based on problem-based learning integrated with Tri-Nga to increase the independence of elementary school students. The research design used in this study is research and development (R&D) with the Borg & Gall model. The data collection techniques used were observation, questionnaires, and interviews. The subjects of this research were fifth grade students of SDN Sumbergiri and SDN Ponjong IV. The object of this research is the improvement of student independence by using the IPAS module based on problem-based learning integrated with Tri-Nga. The results showed that the expert assessment of the Tri-Nga integrated problem-based learning-based IPAS module obtained an average percentage of 93.8% with very feasible criteria. The effectiveness of the module in increasing student independence obtained an average N-Gain percentage of 0.78 with effective criteria. The N-Gain percentage obtained an average value of 77.97 with effective criteria. Based on the results of the study, it can be concluded that the IPAS module based on problem-based learning integrated with Tri-Nga is feasible and effective in increasing the independence of elementary school students.